Padrões filogenéticos dos vertebrados terrestres: implicações para conservação - Batista, Mariana Cristina Gomes (2017)
The accelerated rate of species loss has emerged an increasing number of studies to design effective conservation strategies, considering the limited resources available for biodiversity conservation. In this context, it has been identified conservation priorities, patterns in species vulnerability has been investigated and estimates of biodiversity loss has been performed in attempt to measure the magnitude of the current extinction crisis. Amount of evolutionary history (EH) hold by organisms has been indicated as a suitable measure to estimate the potential damage by possible extinctions, since it incorporates diversity among species. The different applications of EH in conservation studies are briefly reviewed in Chapter 1, showing potential limitations of some approaches. Observations made in chapter 1 detail some benefits of EH loss estimates through sequential extinctions, which simultaneously allow an evaluation of the efficiency of different conservation strategies as well as an identification of priorities. However, rates of EH loss are usually limited to specific taxonomic groups or geographic regions, and are estimated through different methodological procedure and thus limit the power of comparison between results. Circumventing these limitations, Chapter 2 presents estimates of EH loss for terrestrial vertebrates on global and regional scales (cells 1 ° longitude by 1 ° latitude) through sequential extinctions, indicating sites where extinction of threatened species would be greater than expected at random. Although rates of EH loss are equivalent between groups when analyzed globally, we observed incongruent results among the distinct taxonomic groups when investigated regionally. However, the existence of distinct EH metrics has created doubt on the robustness of estimates of EH loss. One concern is the possibility that different EH metrics applied to the same group of species could artificially lead to different conservation strategies. In chapter 3 it was observed that there is quantitative difference in the rate of EH loss between distinct metrics, however the result was not qualitatively different, that is, within our methodological procedure the magnitude of EH loss is equivalent independent of the metric used.